Peningkatan Motivasi Belajar Siswa Menggunakan Media Audio Visual Melalui Pembelajaran Pkn Pada Siswa Kelas IV SD Negeri 178 Tulekko Kecamatan Bontotiro Kabupaten Bulukumba - Nur Aziza; Rismawati Rismawati; Suardi Suardi (Departement of Mathematics Education, 2024)
This research is Classroom Action Research (PTK) which was carried out in two cycles. This research aims to obtain information regarding student learning motivation using audio-visual through Civics learning. The results of the research show that the application of audio visual learning media can improve Civics learning outcomes with evidence of student activity in cycle I with a percentage of 61.66% and then increasing in cycle II with a percentage of 86.66%. Then it was concluded that in cycle I the percentage of student learning outcomes was only 55% with an average of 67 and in cycle II the percentage of learning outcomes was 85% with an average of 78. So the increase in learning outcomes from cycle I to cycle II was 30%. / so that an increase in the results of this test shows that the indicators of success have been achieved